The Existence of Solutions for a Nonlinear Fractional Multi-Point Boundary Value Problem at Resonance. (18th August 2011) - Han, Xiaoling; Wang, Ting
Abstract : We discuss the existence of solution for a multipoint boundary value problem of fractional differential equation. An existence result is obtained with the use of the coincidence degree theory.